2018
DOI: 10.1259/bjr.20170869
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune epilepsy: findings on MRI and FDG-PET

Abstract: Although autoimmune epilepsy (AE) is a relatively new concept in the radiology literature, evidence for immunological mechanisms in epilepsy has increased in the last several years. 1-9 AE was originally described in the context of more generalized autoimmune encephalopathy, predominately as a paraneoplastic phenomenon targeting the limbic system. Certain tumors expressing neuronal proteins were found to provoke a cell-mediated neurological disorder as a byproduct of an attack on cancer cells. The classically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 99 publications
(205 reference statements)
2
33
0
1
Order By: Relevance
“…18 F-Fluoro-deoxy-glucose ( 18 F-FDG) Position Emission Tomography (PET) is a functional brain imaging technique used to visualize neuronal glycolytic metabolic activity which increases during brain in ammation. Importantly, neurological alterations are associated with lower metabolic activity in speci c areas of the brain 15 . 18 F-FDG PET has also been shown to be superior to morphological imaging in the early diagnosis of autoimmune encephalitis 15 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 F-Fluoro-deoxy-glucose ( 18 F-FDG) Position Emission Tomography (PET) is a functional brain imaging technique used to visualize neuronal glycolytic metabolic activity which increases during brain in ammation. Importantly, neurological alterations are associated with lower metabolic activity in speci c areas of the brain 15 . 18 F-FDG PET has also been shown to be superior to morphological imaging in the early diagnosis of autoimmune encephalitis 15 .…”
Section: Introductionmentioning
confidence: 99%
“…18 F-FDG PET has also been shown to be superior to morphological imaging in the early diagnosis of autoimmune encephalitis 15 . The increasing number of publications studying the results of brain 18 F-FDG PET in autoimmune encephalitis over the past decade is in dire need of consolidation [13][14][15][16][17][18][19][20][21][22][23][24] . The literature is saturated with isolated case-reports and retrospective studies conducted on a small number of patients, leaving the role of PET in the initial assessment of the disease unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequential CSF analyses were negative for tumor cells. Although GAD65‐associated encephalopathies usually show significant MRI abnormalities such as temporal lobe involvement, cases with minor MRI alterations (such as in our patient) have also been reported [1,2. Moreover, a recent study by Vogrig et al, in which ICI‐associated CNS side effects were analyzed systematically, showed normal cranial MRI in approximately one‐third of patients with ICI‐induced autoimmune encephalitis [3.…”
Section: Case Reportmentioning
confidence: 56%
“…Compared with MRI with poor sensitivity, FDG-PET showed more evidence in detecting the progressive stages of anti-NMDAR encephalitis [ 61 ]. The metabolic changes on FDG-PET vary widely and involve all the cerebral lobes, including the temporal and occipital lobes, insular cortex, basal ganglia, hippocampi, striatum, caudate nuclei, cerebellum, and brainstem [ 51 , 62 64 ]. The FDG-PET images of anti-NMDAR encephalitis-associated epilepsy showed a pattern of decreased metabolism from the front to the back, that is, high metabolism in the frontal lobe, temporal lobe, and basal ganglia and low metabolism in the parietal occipital lobe, and the metabolic pattern could change with disease progression, treatment, and follow-up [ 63 ].…”
Section: Structural and Functional Neuroimaging Imaging Features Omentioning
confidence: 99%